Interprofessional collaboration (or lack thereof) between faculty and learning technologists in the creation of digital learning - Han, Siew Ping (2024)
Background: As digital learning becomes more prevalent and important in health professions education, learning technologists play increasingly central roles in designing and delivering learning materials. However, little is understood about the process by which learning technologists have integrated into the existing teaching and learning ecosystem, and it seems that they remain marginal and undervalued. Our aim in this paper was therefore to examine the process of interprofessional co-development of course materials as experienced by educators and learning technologists. Methods: Our approach was qualitative, using individual semi-structured interviews (conducted between July 2021 to May 2022) to explore the working relationship between faculty and learning technologists. Transcripts were analysed abductively. Results: We found that the attitudes of both faculty and learning technologists towards collaborating to drive digital adoption in health professions education fell into two main themes: “embrace” and “replace” – and “conflict”, which we present as a third theme. Our results revealed that faculty did not take an active and agentic role in developing their digital practices in respect of education delivery. Learning technologists positioned themselves as a resource to support faculty’s knowledge and skill gap in digital competence. There was an obvious power differential between the two groups: learning technologists lacked agency and seemed in the position of servants to faculty masters. This created barriers to effective collaboration. Conclusions: By examining the process of co-development of course materials by faculty and learning technologists, we open up a space to examine the social, relational and organisational complexities associated with interprofessional collaboration in digital health professions education. Our study also has important implications for guiding educational policy to better position learning technologists to effectively collaborate with faculty and realise the potential of digital health professions education.